Evaluation of Tagetes patula (Asteraceae) as an ecological alternative in the search for natural control of the cattle tick Rhipicephalus (Boophilus) microplus (Acari: Ixodidae) - Politi, Flávio Augusto Sanches [UNESP]; Fantatto, Rafaela Regina [UNESP]; da Silva, Alexander Alves [UNESP]; Moro, Isabela Jacob [UNESP]; Sampieri, Bruno Rodrigues; Camargo-Mathias, Maria Izabel [UNESP]; Figueiredo, Amanda; de Souza Chagas, Ana Carolina; Furlan, Maysa [UNESP] (Springer Nature, 2019)
The cattle tick Rhipicephalus microplus is a great sanitary problem and causes huge losses to livestock, being a vector of important diseases. The aim of this work was to verify the action of plant-derived material obtained from Tagetes patula on the life cycle of R. microplus, as well as to analyze the action of these extracts on ovary cells of engorged females. In the Adult Immersion Test, the crude ethanolic extract (TpEtOH) showed an efficacy of 99.2% (LC50 = 18.60 mg mL−1). From the repellency test, it was found that both the TpEtOH and essential oil were 100% efficient on the larval stage. In addition, in the Larval Package Test, a mortality of 98.37% was obtained with TpEtOH (LC50 = 3.798 mg mL−1). From the microscopic analysis of ovary cells, morphological changes in the chorion and cytoplasm of oocytes were observed, with vacuolization around the germinal vesicle and disorganization of the pedicular cells, suggesting an interference in the normal embryogenic formation of the larvae. These results demonstrate that T. patula extracts interfere at all stages of development of the ixodid, from eggs to adults forms, and have a pronounced repellent effect. In addition, the results of the cytotoxicity assays performed on keratinocytes, as well as previous information on oral and dermal acute toxicity (LD50 > 4000 mg kg−1), attest that T. patula can be a safe alternative for ectoparasitic control, representing an alternative for development of a formulation used to help control populations of ticks in the field.
Keywords: Acaricides; Livestock; Microscopy; Natural products; Spotted fever; Ticks